ANALISIS TINGKAT KEPUASAAN MAHASISWA TERHADAP FASILITAS PEMBELAJARAN DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS RIAU - Refiyandi Muhammad; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the level of satisfaction of FKIP students with learning facilities at FKIP University of Riau. The population used in this study were FKIP University of Riau students class 2017, 2018, and 2019. Data collection techniques were carried out by distributing questionnaires using a Likert scale. Samples were taken as many as 361 students from 3753 students, using the Slovin formula to determine the number of samples used. The collected data is then tabulated and analyzed using themethod Importance Performance Analysis (IPA). The results showed that the average value of the attribute suitability level was 58.59% from 100%. From the level of suitability of these attributes, it can be concluded that the FKIP University of Riau students were not satisfied with the learning facilities at the FKIP University of Riau.Key words: Student Satisfaction, Learning Facilities